2020
DOI: 10.20435/inter.v21i2.2337
|View full text |Cite
|
Sign up to set email alerts
|

Padrões alimentares e (in)segurança alimentar e nutricional no Programa Bolsa Família

Abstract: O Programa Bolsa Família (PBF) apresenta diversos efeitos na população com riscos e vulnerabilidades sociais, principalmente em relação à alimentação, educação e saúde. O objetivo foi identificar padrões alimentares de famílias beneficiárias ou não do PBF em município paulista, analisando sua associação com níveis de insegurança alimentar (IA). O estudo incluiu 150 famílias. Aspectos socioeconômicos, demográficos, antropométricos e de consumo alimentar foram avaliados por meio de questionários validados. A IA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
1
0
1
Order By: Relevance
“…Just like in our study, adherence to an unhealthy foods dietary pattern in individuals of higher socioeconomic status was observed in other studies [23,24]. Higher socioeconomic status is not necessarily associated with a diet of better nutritional quality, as factors such as individual food preferences and regional eating habits can influence food intake [26].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Just like in our study, adherence to an unhealthy foods dietary pattern in individuals of higher socioeconomic status was observed in other studies [23,24]. Higher socioeconomic status is not necessarily associated with a diet of better nutritional quality, as factors such as individual food preferences and regional eating habits can influence food intake [26].…”
Section: Discussionsupporting
confidence: 85%
“…Some studies found that this pattern was more adhered to by females, while others studies found that it was more adopted by males [4,[22][23][24]. This finding can be justified by the fact that females are more physically inactive compared, which can lead to greater consumption of low nutritional value foods such as those included in the "Western" dietary pattern [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…É importante ressaltar que mulheres em idade fértil representam um grupo de alta vulnerabilidade para o desenvolvimento de deficiências nutricionais e a presença da IAN neste período aumenta ainda mais estes agravos, sendo necessárias estratégias intersetoriais de promoção à SAN no contexto da APS, porta de entrada dos serviços do Sistema Único de Saúde (CARDOZO et al, 2020).…”
Section: Resultsunclassified